Icariin improves cognitive deficits by reducing the deposition of β-amyloid peptide and inhibition of neurons apoptosis in SAMP8 mice. Issue 9 (10th June 2020) - Wu, Jie; Qu, Jing-Qiu; Zhou, Yan-Jun; Zhou, Yong-Jian; Li, Yuan-Yuan; Huang, Nan-Qu; Deng, Cheng-Min; Luo, Yong
Abstract : Effective therapeutic drugs for prevent or reverse the pathobiology of Alzheimer's disease (AD) have not been developed. Icariin (ICA), a prenylated flavonol glycoside derived from the traditional Chinese herb Epimedium sagittatum, exerts a variety of pharmacological activities and shows promise in the treatment and prevention of AD. This study investigated the neuroprotective effects of ICA in SAMP8 mice model of aspects of early AD and explored potential underlying mechanisms. Our results showed that intragastric administration of ICA could reverse the learning and memory impairment of SAMP8 mice in the Morris water maze. Western blot of hippocampal specimens revealed that ICA down-regulated the expression of BACE1 to reduce the expression of cytotoxic Aβ1-42 . Furthermore, ICA siginificantly increase the Bcl-2/Bax ratio by increasing the expression of anti-apoptotic protein Bcl-2, and decreasing the expression of pro-apoptotic protein Bax, and thus inhibit neurons apoptosis. These findings indicate that ICA could improve cognitive deficits by reducing the deposition of β1-42 and inhibition of neurons apoptosis and provide further evidence for the clinical efficacy of ICA in the treatment of AD.